Effects of Varied Versus Constant Loading Zones on Muscular Adaptations in Trained Men - Schoenfeld, B. J.; Contreras, B.; Ogborn, D.; Galpin, A.; Krieger, J.; Sonmez, G. T. (International Journal of Sports Medicine, 2016)
The purpose of this study was to compare the effects of a protocol employing a combination of loading zones vs. one employing a constant medium-repetition loading zone on muscular adaptations in resistance-trained men. 19 trained men (height=176.9±7.0 cm; body mass=83.1±11.8 kg; age=23.3±2.9 years) were randomly assigned to 1 of 2 experimental groups: a constant-rep resistance training (RT) routine (CONSTANT) that trained using 8–12 RM per set, or a varied-rep RT routine (VARIED) that trained with 2–4 RM per set on Day 1, 8–12 RM per set on Day 2, and 20–30 RM on Day 3 for 8 weeks. Results showed that both groups significantly increased markers of muscle strength, muscle thickness, and local muscular endurance, with no differences noted between groups. Effect sizes favored VARIED over CONSTANT condition for elbow flexor thickness (0.72 vs. 0.57), elbow extensor thickness (0.77 vs. 0.48), maximal bench press strength (0.80 vs. 0.57), and upper body muscle endurance (1.91 vs. 1.28). In conclusion, findings indicate that both varied and constant loading approaches can promote significant improvements in muscular adaptations in trained young men.
Keywords: loading zones; repetition range; muscle hypertrophy; maximal strength; muscular endurance